UPAYA PENINGKATAN PEMBELAJARAN LARI JARAK PENDEK 80 METER MELALUI MODEL BERMAIN PADA SISWA SD - Budiarto, Herry; Haetami, Mimi; Hidasari, Fitriana Puspa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractProblems in this research is whether learning model play can promote learning run a short distance at grade students five public elementary school 4 tanjung beringin kabupaten melawi. Method in this research using the kind of research the act of class. A subject in this research is students class five public elementary school 4 tanjung beringin kabupaten melawi as many 20 students.The results obtained from research is the results of the assessment of understanding cognitive students on cycle 1 reached 63% (enough good), 2 on the cycle reached 67% (good). The results of observations on the cycle of psychomotor 1 obtained 77%, on cycle 2 92,4% (good), 2 0n the cycle value 94,3% (good). Assessments of students cycle kuisioner on 1 reached 86% with the criteria of good, 2 on the cycle reached 88% with the criteria of good.Keywords: The activity of teachers, learners approach a method of play.